Cross‐reactivities of non‐homologous allergens. Issue 5 (18th May 2020) - Bublin, Merima; Breiteneder, Heimo
Abstract: Allergen cross‐reactivities occur when IgE antibodies, originally raised against a specific allergen, bind to identical or highly similar surface areas of another related allergen. It is a commonly held view that cross‐reactivity requires more than 70% sequence identity, while proteins that share <50% sequence identity are rarely cross‐reactive. This also implies that cross‐reactive proteins have a similar 3D fold and belong to the same protein family. At first, the existence of cross‐reactivity between non‐homologous allergens was not expected because it was contrary to the above described concepts. Now, several lines of evidence demonstrate that IgE cross‐reactivity also exists between unrelated allergens. In this Editorial, we aim to summarize the existing literature on IgE cross‐reactivity between non‐homologous allergens.